Use of biodigesters, cisterns and desalinators: social technologies as sustainable alternatives of coexistence with the Semiarid - Alcócer, Juan Carlos Alvarado; Pinto, Olienaide Ribeiro de Oliveira; Costa, Maria Dasdores Gonçalo; Silva, Maria Elanny Damasceno; Oliveira, Jangirglédia de; da Fonseca, Aluísio Marques (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
The work studies biodigestors, cisterns and desalinizers as sustainable alternatives to coexist with the semi-arid region, seeking to understand how it is possible to benefit rural populations from the production and use of social technologies. The methodology consists of bibliographical surveys from case studies and field studies on the use of these technologies in the semi-arid region. Experiences of use were selected in the municipalities of Barreira, Ocara, Redenção and Ibaretama in the state of Ceará. In the biodigestor is contextualized the most used models at Brazil and the semiarid, with emphasis on the models adopted in the municipalities of Barreira, Ocara and Redenção. In addition, to address the importance of the use of biogas and biofertilizer. In the cisterns, the types that were used in the semi-arid region were verified and the experience of the tanks program in the municipality of Ibaretama was mentioned. In the case of desalinators, the relevance of desalination systems for populations living in water scarcity was discussed, identifying the current equipment panorama installed in Barreira. As results, it was observed that it appears as a solution to meet the basic needs of populations with water supply. Biogas can be used to replace cooking gas and biofertilizer as fertilizer for plants. To do so, it requires greater attention from the public power and active involvement of the population. It is concluded that these technologies are feasible, adaptable to rural property, simple and low cost, since they tend to solve social and structural problems, besides generating income and quality of life for the populations.